A mathematical model for predicting the cutting energy of cocoyam (Colocasia esculenta) - Asonye, G. U.; Asoegwu, S. N.; Maduako, J. N.; Madubuike, C. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Information on the optimum energy requirements for cutting vegetables is useful in order to estimate the amount of energy needed to cut given products with known physical characteristics. This will aid engineers and product designers in the development of appropriate cost effective cutting systems consuming minimum amount of energy while still providing high quality cut products. In this study, predictive equations were developed for describing the cutting energy of cocoyam (Colocasia esculenta) cormels. Dimensional analysis based on the Buckingham pi theorem was used to obtain the functional relationship between the cutting energy of the selected vegetable and the independent variables such as tool weight (w), height of tool drop (Hd), tool edge thickness (t), cutting speed (v), crop size(s), crop moisture content (φ), crop contact area (A) and crop density (σ). The developed model was validated with experimental data and a high coefficient of determination of R2 = 0.982 between the predicted and measured values was established. The obtained predictive model proved appropriate for determining the cutting energy required for cocoyam cormels up to 98%.